Time to change? Technologies of futuring and transformative change in Nepal's climate change policy. Issue 6 (18th August 2021) - Forsyth, Tim
ABSTRACT: This paper calls for a more critical analysis of implicit social values in time-based projections of transformative change in climate change policy in developing countries. The paper argues that transformative change is a form of socio-technical imaginary, in which contemporary visions of social order influence supposedly technical, and apolitical policies and timelines. To analyse these imaginaries, the paper applies the framework of 'technologies of futuring', or the processes in which projections about the future are imbued with implicit values, to different theories of change used to propose responses to climate change in Nepal. The paper shows that projections of future change are linked to assumptions about physical risks and social agency that reflect different, and contestable, worldviews. This chapter concludes that discussions about transformative change need to make assumptions about risk and society more transparent when proposing urgent deadlines based on assumptions about the future.